Efektivitas Pengelolaan Alokasi Dana Desa Untuk Program Pembangunan Desa Dan Pemberdayaan Masyarakat (Studi Pada Desa Pukat, Kecamatan Utan Kabupaten Sumbawa) - Kurnianti, Ari; Inapty, Biana Adha; Suryantara, Adhitya Bayu (Fakultas Ekonomi dan Bisnis Unram, 2024)
This study aims to find out the extent of the effectiveness of the management of Village Funds (DD) in the village development program and community empowerment of Pukat Village, Utan District, Sumbawa Regency. The research method used in this study is qualitative descriptive. To obtain information, the author conducts observations, interviews, and documentation. The effectiveness of village fund management in the implementation of development and community empowerment programs in Pukat Village, Utan District, Sumbawa Regency has been effective. This can be seen from the achievement of goals in the realization of the 2020-2023 budget in accordance with the plan as stated in the RPJMDes. To convey the disclosure of village financial information, the Pukat Village government conducts hamlet or village deliberations, as well as socialization through the installation of billboards. Furthermore, the Pukat Village government has been able to adjust itself in managing village funds in accordance with the problems and needs of the community, as well as regulatory changes, especially during the Covid-19 pandemic